Subalternity in Mariama Diallo's Master. (2022) Movie: Spivak's Subalternity - Renata, Margareta Vania; Mustofa, Ali (ppjbsip, 2023)
There are still subalterns in the contemporary world. Human rights campaigns are widely spread both online and offline. Nonetheless, even when it is not openly evident, discrimination and the subjugation of some races, also known as racism, still exist and are frequently faced on a daily basis. This study explores the racism and discrimination against subalterns that persist at the